SAT0590-HPR Functional Limitations in Patients with Generalized Osteoarthritis. (23rd January 2014) - Cuperus, N.; Vliet Vlieland, T.; van den Ende, C.
Abstract : Background: Physical functioning is one of the core outcomes in clinical practice and research in osteoarthritis (OA). Although individuals with generalized osteoarthritis (GOA) represent a relatively large subgroup of patients, the clinical burden in terms of limitations in physical functioning in this patient group is largely unknown. Objectives: To describe the nature and severity of functional limitations in patients with GOA according to the International Classification of Functioning, Disability and Health (ICF) component Activities and Participation (d-codes). Methods: Baseline data from a randomised controlled trial comparing two non-pharmacological treatment programmes in 128 patients (86% female; mean age (SD) 60 (7.7) years) with GOA were used. GOA was defined as having complaints in three or more joint groups, having at least two objective signs that indicate OA in at least two joints and being limited in daily functioning. The number of painful joint groups was assessed by patient self-report using a paper manikin including eight joint groups. Functional limitations were assessed by the Health Assessment Questionnaire (HAQ), the SF36 subscale physical functioning and the patient specific functional scale (PSFS). In the latter, every patient was asked to report the three most important activities difficult to perform due to GOA and to rate their severity on a 10 cm VAS. Subsequently, these activities were linked to the most precise ICF component (3 rd or 4 th level) by using established ICF linking rules 1 . This was done independently by three researchers. The resulting ICF codes were then compared and disagreements were discussed until consensus was achieved. Results: The median number of painful joint groups was 5 (interquartile range 4-6). Joint groups most often affected were the hands (108, 84%) and knees (105, 82%). Mean (SD) HAQ score and SF-36 physical functioning score were 1.27 (0.50) and 43 (18), respectively. One patient reported two activities difficult to perform, whereas all the other patients were able to identify three functional limitations. The 383 activities obtained with the PSFS were linked to 405 ICF codes within the Activities and Participation component. Of these 405 codes, 270 (67%) pertained to the chapter mobility (d4), 79 (20%) to domestic life (d6), 24 (6%) to community, social and civic life (d9) and 18 (4%) to self-care. The most frequently identified ICF codes and corresponding mean severity scores are presented in hierarchical order in the table . Conclusions: The results indicate that in patients with GOA who have limitations in physical functioning, limitations in activities concerning mobility and domestic life appear to be most frequent and severe. Insight into the severity and spectrum of activity limitations in GOA can be used to develop tailored treatment for this subgroup of patients. References: Cieza et al. (2002). J Rehabil Med;34:205-1 Disclosure of Interest: None Declared